STUDY ON MORTALITY, CULLING AND REPLACEMENT INDEX OF NELLORE SHEEP IN AN ORGANIZED FARM - I. Satish Kumar; C. Vijaya Kumar; G. Gangaraju (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The mortality, culling and replacement Index are important indicators to assess the efficiency of management followed in any organized farm. The present data was collected onNellore Sheep at Livestock Research Station, Palamaner from the available records for 15 years (2000-01to2014-15) and analyzed. The results indicated that the over all mortalityrate was high in adults 5.75% , followed by 6-12 months age (5.18%), 3-6 months age (4.43%) and 0-months age(4.31%). The overall culling rate was also high in adults 9.05% followed by 6-12 months age (4.25%), 3-6 months age (0.70%) and 0-3 months age (0.15%). The annual replacement index varied ranged from 0.54 to 2.44 with an overall average of 1.11 indicating that there is almost one female replaced in breeding stock for loss of one adult female.